Study of Lipid Profile in Diabetes Mellitus with and without Hypertension (Journal of Basic and Applied Research in Biomedicine, 2022)
Introduction Alterations in the lipid metabolism have been reported in the subject of diabetes mellitus. They may be influenced by the presence of hypertension. Aims The present study was undertaken to estimate the serum lipids profiles of diabetics with and without hypertension. Study design The study design is experimental with comparative study method, Methodology The sample size taken is 80 which is divided into four groups as A group of 20 healthy individuals of age 20-70 years, other B group of 20 diabetic patients without Hypertension, other C group of 20 hypertensive patients without diabetes and the rest 20 diabetic patients along with hypertension of age 20-70 years of D group. They were matched with respect to various lipid parameters such as total cholesterol, Triglycerides, β: α lipoprotein ratio etc. with control group A. Place and duration of study: the study took place at Santosh group of institutions between August 2013 to August 2016. Result The serum cholesterol levels were significantly higher in hypertensives without diabetics and in diabetics with hypertension as compared to normal controls. No significant difference in the serum triglyceride level was observed among various groups in this study. The β: α lipoprotein ratio was found to be affected in all the groups as compared to controls with maximum ratio in diabetics without hypertension and in hypertension without diabetes. Patients who were suffering from diabetes and hypertension were at a maximum risk of developing atherosclerosis and its complications such as coronary artery disease. Diabetics with hypertension had significant higher levels of cholesterol as compared to that of without hypertension. The diabetics with hypertension had lipid abnormalities because of diabetic element in them rather than the hypertension. All the groups studied except the controls were found to be increasingly susceptible to the risk of atherosclerosis and its complications. This risk was found to be maximum in diabetics with hypertension rather than diabetics or hypertensive’s alone. Conclusion The need for right balanced diet, regular exercise and a stress free life is essential for prevention and management of diabetes and hypertension